Síntese de derivados de benzo[b]furano promovida por t-BuOK - Pinheiro, Roberto do Carmo (2023)
In this work, we report the study developed for the preparation of benzo[b]furan derivatives via intramolecular double cyclization reaction promoted by tert-BuOK. First, 3- ((butylselanyl)methyl)-2-(phenylethynyl)benzofuran and 3-methyl-2- (phenylethynyl)benzofuran derivatives were selectively synthesized by reacting 1- (phenylethynyl)-2-((2-(phenylethynyl)benzyl)oxy)benzene with t-BuOK in different solvents. Furthermore, 4-iodo-3-phenyl-1H-selenopyrano[4,3-b]benzofuran derivatives were synthesized through further iodocyclization. In the second half of this work, 1-(phenylethynyl)- 2-((2-(phenylethynyl)benzyl)oxy)benzene derivatives were subjected to a tandem carbocyclization reaction with t-BuOK, leading to the synthesis of 6,7-diphenyl- 5Hbenzo[6,7]cyclohepta[1,2-b]benzofurans in good yields. Both elaborated methodologies took place selectively through a 5-exo-dig intramolecular cyclization for the formation of benzo[b]furans and, in the second half of this work, a 7-endo-dig cyclization, providing the benzo[b]furans fused to a 7-membered carbocycle in a one-pot procedure.